Socioeconomic, physical and mental health impacts of climate change among informal outdoor workers in sub-Saharan Africa: A scoping review protocol - Sylvia Hagan; Kate Nyhan; Ernest Darkwah; Collins Badu Agyemang; Yaw Agyeman Boafo (PLoS ONE, 2026)
The informal economy plays a critical role in Sub-Saharan Africa (SSA), yet informal outdoor workers are disproportionately exposed to climate-related hazards. Existing reviews often merge formal and informal workers, limiting insight into the distinct vulnerabilities and outcomes experienced in informal outdoor work. This proposed scoping review seeks to synthesise evidence on the socioeconomic, physical, and mental health impacts and coping strategies of climate change among informal outdoor workers in SSA. We will search Medline, Global Health, Embase, Scopus, Lens, PsycINFO, Business Source Complete, African Journals Online (AJOL), and Africa Index Medicus, alongside grey literature searching and citation tracking. We will include primary studies published in English (2015–2025) reporting qualitative, quantitative, or mixed-method findings. Screening and extraction will be conducted in duplicate, with discrepancies resolved by team members. Findings will be reported following PRISMA-ScR and synthesised narratively and thematically. Results will be disseminated through peer-reviewed publications, conferences, and webinars.